Evaluation of Category I of Anti-tuberculosis Therapy in Intensive Phase Pulmonary TB by Conversion of Acid-Fast Bacilli Sputum - Putra, Oki Nugraha; Damayanti, Amitasari; Nurrahman, Nani Wijayanti Dyah; Devi, Tsania; Aluf, Wildatul (Pharmaceutical Sciences and Research, 2019)
Acid fast bacilli (AFB) sputum microscopy is used to diagnose tuberculosis (TB) and to evaluate the effectiveness of anti-tuberculosis drugs in TB eradication program. The AFB sputum microscopy should be performed before treatment, two months after intensive phase and four months after advance phase treatment. The aim of this study was to evaluate the sputum conversion rate of AFB in pulmonary TB patients who received category I of antituberculosis (anti-TB) drugs. Evaluation of sputum conversion was perfomed before initation of anti TB drugs and at the end of the intensive phase. This cohort prospective study was done from February to May, 2018. Nine pulmonary TB patients fulfilled the criteria during the study. This AFB sputum microscopy was evaluated by using Ziehl Neelsen and read by means of International Union Against Tuberculosis and Lung Disease (IUATLD) scale. Nine sputum smear positive were followed for two months. After two months (end of the intensive phase), the smear conversion rate was 100%. All patients received standard dose of anti-TB drugs in fix dose combination (FDC). It can be concluded that the sputum conversion of AFP in pulmonary TB patients who received category I of anti-TB was success at the second month of intensive phase.